Analys av undervisning i spontant uppkomna situationer i förskolan - Carina Hjelmér; Maria Rönnlund; Anna Olausson (Educare)
This article explores preschool teachers’ experiences of conducting analysis of their own and each other’s spontaneously arising teaching situations. Grounded in an ecological perspective on teachers’ agency, the study addresses two central questions: (1) What prerequisites appear to be essential for enabling preschool teachers to conduct analysis of teaching in spontaneous situations? (2) What insights do preschool teachers gain through such analyses, and how do these contribute to developing their teaching? The study draws on a one-year Swedish research and development project involving three researchers and 50 preschool teachers. Data were collected through notes documented by both researchers and preschool teachers. Key prerequisites identified include access to continuing professional development, opportunities for collaborative reflection work, and dedicated time for analysis. The use of an analysis tool aligned with teachers’ perceptions of core preschool values and practices also proved beneficial. Through their analysis, teachers gained awareness of their own interactions with the children and the children’s interests. However, connecting spontaneous situations to specific curriculum goals emerged as more of a challenging aspect of the process.